Organic waste recycling application increases N availability and mitigates N2O emission without crop yield penalty in the North China Plain - Chen, Lin; Du, Hailun; Liu, Qing; Gao, Wangsheng; Cui, Jixiao; Chen, Yuanquan (Frontiers in Plant Science, 2024)
Agricultural organic waste recycling can supply nutrients for crop production and partially replace chemical nitrogen fertilizers, which is beneficial for waste management and environmental protection. Nevertheless, comprehensive evaluation for the effects of different organic materials application on crop yield and environment are limited. Therefore, in this study, a comprehensive investigation on the synergistic effects of straw, pig manure, and biogas residue recycling on the wheat (Triticum aestivum L.) and maize (Zea mays L.) systems was carried out in the North China Plain.Field experiments were conducted from 2019 to 2021, comprising five treatments: straw (ST), pig manure (PM), and biogas residue (BR) partially replacing chemical nitrogen fertilizer, sole application of chemical nitrogen fertilizer (CF), and a control with no nitrogen application (WN).The results showed that organic materials significantly increased soil total nitrogen (3.04%-9.10%) and N recovery efficiency (REN, 42.21%-44.99%), but pig manure was more beneficial to increase crop yields (3.50%), especially wheat yields (8.72%), and REN was significantly higher than that of the other treatments. Organic materials performed differently in wheat and maize seasons, and wheat yield could be improved by organic materials return. Organic materials stimulated N2O emission in wheat season (4.28%-32.20%), while biogas residue inhibited the N2O emission in maize season (47.47%). The negative effect of straw and biogas residue on yield decreased with increasing years of return, and pig manure continued to contribute to yield. In conclusion, pig manure is the optimal alternative that can increase crop yield, soil N content and REN without stimulating N2O emissions.